Rheumatoid arthritis: Treatment evolution over the years - Eleftherios Pelechas; Panagiota Karagianni (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2020)
Rheumatoid arthritis (RA) is a systemic, inflammatory autoimmune disorder affecting approximately 0.5-1% [1] of the general population. It is characterized by inflammation and proliferation of the synovial lining, leading to destructive changes within the synovial-lined joints [2], especially if left untreated. Patients suffering from RA, usually complain about pain and swelling of the affected joints as well as morning stiffness in and around the joints, lasting at least 1 hour before maximal improvement [3].